Mimicking anatomical condylar configuration into knee prosthesis could improve knee kinematics after TKA — A computational simulation - Liu, Yu-Liang; Chen, Wen-Chuan; Yeh, Wen-Ling; McClean, Colin Joseph; Huang, Chun-Hsiung; Lin, Kun-Jhih; Cheng, Cheng-Kung (Clinical biomechanics (Bristol), 2012)
Restoration of femoral rollback and tibial internal rotation are two of the major objectives following total knee arthroplasty. Previously, we improved prosthetic knee kinematics by replicating the convexly lateral tibial plateau of intact knee. This study attempted to regain more normal knee kinematics through a posterior cruciate ligament retaining knee, which simultaneously incorporated convexly lateral tibial plateau and anatomical condylar configuration into the prosthesis design. Computational simulation was utilized to analyze motion of three-dimensional knee models. Three total knee systems with consistent convex insert design but with different condylar heights of 0, 2.7 and 4.7mm were investigated in present study. Magnetic resonance images of the subject were utilized to construct the bone models and to distinguish the attachment sites of ligaments and tendons. The distal femurs were modeled to rotate about designated flexion axes of femoral components, and the motion of the proximal tibia was unconstrained except further activity of flexion/extension. Movements of the medial/lateral condyles and tibial rotation were recorded and analyzed. Significant improvements in posterior movement of the lateral condyle and in tibial internal rotation were observed for knee models with different condylar heights, as compared to the knee model with consistent condylar height, when flexion exceeded 100°. Results also revealed that excessive difference in condylar height over anatomical condylar configuration provided no contribution to the restoration of normal knee kinematics. Replicating the morphology of anatomical condylar configuration of the intact knee into knee prostheses could improve knee kinematics during higher knee flexion.